2023
DOI: 10.3390/pharmaceutics15030789
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Peptides: Avant-Garde Antifungal Agents to Fight against Medically Important Candida Species

Abstract: Expanding the antifungal drug arsenal for treating Candida infections is crucial in this era of the rising life expectancy of patients with immunosuppression and comorbidities. Infections caused by Candida species are on the rise, including those caused by multidrug-resistant strains or species, and the list of antifungals approved for the treatment of these infections is still limited. Antimicrobial peptides (AMPs) are short cationic polypeptides whose antimicrobial activity is under intense investigation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 149 publications
0
10
0
Order By: Relevance
“…28,29 Regarding the secondary structures, AMPs are classified as linear α-helical peptides, β-sheet peptides, peptides with extended structure, and peptides with both α-helix and β-sheet conformation or with more complex topologies. 30 Based on their biological activity, we can distinguish between AMPs with antibacterial, 31 antifungal, 32 antiviral, 33 antiparasitic, 34 and anticancer properties. 35 Based on their primary mechanism of action, AMPs can be divided in two major groups: non-membrane targeting and membrane targeting AMPs, even if recent evidence showed that some AMPs not only act on the membrane but they can also activate a cascade of reactions within bacterial cells.…”
Section: The Need For New Antiviral Compounds and The Potential Of Ampsmentioning
confidence: 99%
“…28,29 Regarding the secondary structures, AMPs are classified as linear α-helical peptides, β-sheet peptides, peptides with extended structure, and peptides with both α-helix and β-sheet conformation or with more complex topologies. 30 Based on their biological activity, we can distinguish between AMPs with antibacterial, 31 antifungal, 32 antiviral, 33 antiparasitic, 34 and anticancer properties. 35 Based on their primary mechanism of action, AMPs can be divided in two major groups: non-membrane targeting and membrane targeting AMPs, even if recent evidence showed that some AMPs not only act on the membrane but they can also activate a cascade of reactions within bacterial cells.…”
Section: The Need For New Antiviral Compounds and The Potential Of Ampsmentioning
confidence: 99%
“…AMPs are small polypeptides (mostly positive charged, + 2 to + 7) with 2–50 amino acid residues isolated from virtually all life forms. Biologically, they are synthesized mainly in ribosomes and may undergo post-translational modifications, with current techniques of protein synthesis being used for the large-scale production of synthetic peptides [ 79 ]. AMPs are part of the organism’s innate immune response.…”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%
“…AMPs involved in antimicrobial activity against bacteria and viruses have been widely studied, although therapeutic strategies to control fungal diseases with these molecules have still been limited [ 79 ]. The manipulation of the immune system for the development of vaccines against fungi, activation of the specific immune response directed to fungal agents (in the form of targeted stimulation of phagocytes, T cells, and antibodies), as well as the induction of the innate or adaptative immune response, with the manipulation of the profile of cytokines, constitute a challenge for therapeutic innovation, with data in the literature being less frequent than those found for bacteria and viruses [ 92 , 93 ].…”
Section: Antimicrobial Peptides (Amps)mentioning
confidence: 99%
“…Together, this highlights the growing need for the development of new drugs with different mechanisms of action as well as for the search of novel approaches to treat infections caused by commonly occurring pathogenic species. During the last few decades, several antimicrobial peptides (AMPs) have been under intense investigation to be used as standalone or in combination therapies against invasive fungal infections ( Rodriguez-Castano et al., 2023 ). These small cationic and amphipathic molecules, typically consisting of less than 50 amino acids, form part of the primary line of defense against pathogens of many organism ( Matejuk et al., 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, this study aims to evaluate C14R as a potential new AMP against the prevalent opportunistic yeast C. albicans and the emergent multidrug-resistant yeast C. auris . Most studies evaluating the effect of AMPs in species of Candida have included only a few reference strains per species ( Rodriguez-Castano et al., 2023 ). However, to our knowledge, this is the first study evaluating a large set of clinical isolates of both C. albicans and C. auris , which allows to estimate epidemiological cutoff values (ECVs) that help determining whether each species, as a population, has good or poor in vitro response to C14R as antifungal agent ( Lockhart et al., 2017 ).…”
Section: Introductionmentioning
confidence: 99%